Lost in Translation—and Transmission: Contrasting Chinese and U.S. Gymnastics Television Coverage in the 2016 Rio Olympic Games. (2nd September 2018) - Billings, Andrew; Xu, Qingru; Angelini, James R.; MacArthur, Paul J.
Abstract : Gymnastics is one of the most popular sports at the Summer Olympics in both the United States and China. This study content analyzes more than 23 hours of Olympic gymnastics at the 2016 Rio Games on NBC and CCTV, examining potential framing differences pertaining to nationality and biological sex. Findings reveal that, in terms of name mentions, NBC favored female and domestic gymnasts, yet CCTV devoted more mentions to male and nondomestic gymnasts. Regarding word-by-word descriptors, multiple significant differences strongly suggest that the two networks depict gymnasts in substantially different manners. Discussions and research directions are also offered.